2021
DOI: 10.3389/fonc.2021.641975
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Cost-Minimization Analysis of Continuous Infusion of Low-Dose Gemcitabine Plus Cisplatin in Patients With Unresectable Malignant Pleural Mesothelioma

Abstract: BackgroundMalignant pleural mesothelioma (MPM) is rare and aggressive neoplasia, with a poor prognosis; furthermore, the monetary cost of its treatment represents a major challenge for many patients. The economic burden this malignancy imposes is underscored by the fact that asbestos exposure, which is the most frequent risk factor, is much more prevalent in the lower socioeconomic population of developing countries. The aims of the present study were to evaluate the efficacy, safety, and cost of continuous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 29 Most of the existing economic studies on MPM focused on chemotherapy. 30 32 In 2012, Woods et al ., on the basis of the results of the EORTC08983 trial, used an indirect comparison method to evaluate the relative efficacy of raltitrexed combined with cisplatin and pemetrexed combined with cisplatin. They concluded that raltitrexed in combination with cisplatin was an economical first-line treatment for patients with MPM.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Most of the existing economic studies on MPM focused on chemotherapy. 30 32 In 2012, Woods et al ., on the basis of the results of the EORTC08983 trial, used an indirect comparison method to evaluate the relative efficacy of raltitrexed combined with cisplatin and pemetrexed combined with cisplatin. They concluded that raltitrexed in combination with cisplatin was an economical first-line treatment for patients with MPM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, survival outcomes predicted for different CALGB groups in this study were slightly different from those previously reported in different cohorts, which may be attributed to variations in their therapeutic management ( 25 ). In this regard, our cohort underwent standard treatment with cisplatin and pemetrexed, but better clinical outcomes have been described in previous evidence by combining chemotherapy with bevacizumab ( 19 ), pembrolizumab ( 26 ), gemcitabine as continuous infusion ( 27 ), liposomal doxorubicin ( 28 ), or substituting it with ipilimumab plus nivolumab ( 6 ). In contrast, lack of benefit has been identified in unresectable epithelioid MPM after monotherapy with CTLA-4 ( 29 ) as second-line of treatment or VEGF ( 30 ) blockers as first-line approach.…”
Section: Discussionmentioning
confidence: 93%
“…The loss of the BAP1 protein is a common occurrence in mesothelioma, particularly in the epithelioid/biphasic subtypes, often linked to homozygous BAP1 deletion. BAP1 immunostaining from pleural fluid serves as an outstanding biomarker, exhibiting a 100% specificity in distinguishing between benign and malignant mesothelial proliferations [52,53], making it a valuable rule in test.…”
Section: Role Of Brca Associated Protein 1 (Bap-1) Immunohistochemistrymentioning
confidence: 99%
“…Gemcitabine, when combined with a platinum compound like cisplatin, carboplatin, or oxaliplatin, has undergone extensive testing in numerous phase II studies, showing variable response rates with acceptable toxicity levels [70][71][72]. Arrieta et al [52] highlighted its efficacy, safety, and cost-effectiveness, particularly noting that Gemcitabine plus cisplatin is a viable and safe treatment for patients with unresectable MPM [47]. Carboplatin is an alternative when cisplatin is unsuitable.…”
Section: Unresectable Diseasementioning
confidence: 99%